PELAYANAN KESEHATAN PEDULI REMAJA (PKPR) DENGAN MENCIPTAKAN KONSELOR SEBAYA DI MAN DUMAI DAN SMKN 3 DUMAI - salmiati salmiati; Rini Hariani Ratih; Maria Arani (LPPM Universitas Abdurrab, 2018)
ABSTRACT Adolescents are individuals who are undergoing a transitional period, which in terms of biological maturity, sexual being gradually show the characteristics of secondary sex until the maturity of sex. Various problems that occur in adolescents are influenced by various dimensions of life within them, both biological, cognitive, moral and psychological dimensions and the influence of the surrounding environment. In realizing healthy teenagers, one of the government's efforts is with the establishment of Youth Care Care Program (PKPR). The Purpose of Community Service Activity to Provide Care for Youth Care (PKPR) by providing information and education through counseling then provides an opportunity for interested and talented teenagers to attend peer educator training and peer counselors in a closed room. Methods of dedication to this community by doing counseling and training to become a teen counselor. The results of student devotion are very enthusiastic in the activity and there are some students who have the talent of being a teen counselor. In realizing healthy teenagers, one of the government's efforts is with the establishment of Youth Care Care Program (PKPR). Types of PKPR activities include counseling, medical clinical services including investigation, counseling, healthy life skills education (PKHS), peer educator training (trained into adolescent health cadres) and peer counselors (peer educators who are provided with additional interpersonal relationship and counseling training) , as well as referral services. Key words: Health Care for Youth Care (PKPR), Youth Counselor